(untitled) (Teaching and Learning Inquiry, 2020)
This article offers narratives of individual journeys through the scholarship of leading in three different contexts—Asia, Europe, and Africa. Together, these narratives argue for the need to make explicit the diversity of practices of the scholarship of teaching and learning (SoTL), with each practice inextricably tied to specific geographical, sociocultural, and political contexts. In offering these contextual specificities, we call on all who engage in SoTL to exercise reflexivity in thought, language, and action—to actively foreground our mental models and assumptions about SoTL and what it looks like for ourselves and for others; to sensitively engage scholars who do not share our context; and to strive toward an inclusive mindset and practice that will situate all of us within the “international” of an international organization. We highlight the problems of language, meaning, and translation; and the challenge scholars from “different shores” face in engaging with “other” shores.